The Impact of Social Capital to the Health of Elderly: the Case Post-Tsunami Aceh in 2004 - Rovidah, Dzakyatur; Pangaribowo, Evita Hanie; Hardiyanti, Wida Reza (Universitas Gadjah Mada, 2025)
Social capital has been considered an important factor on mental and physical health. However, thereis no consensus on its best measurement. This research examines the effect of informal social capital (family and community support) on the health quality of the elderly through self-assessed health status (SAHS), self-care ability (ADL), and mental health (PTSD). This study introduces the use of instrumental variable (IV) estimation to address endogeneity in evaluating social capital’s effect on elderly well-being in the context of post-tsunami Aceh. Utilizing secondary data from the 2022 STAR survey, the study applies a quantitative approach with an IV probit model to analyze the impact of social capital on binary health outcomes (SAHS, ADL, PTSD). Instrumental variables include residence status, number of social networks, and life satisfaction chosen for their correlation with social capital but exogeneity with health outcomes. Tests for endogeneity, weak instruments, and over-identification were conducted to validate the analytical framework. This research found that informal social capital significantly improves physical health (SAHS and ADL) and mental health (PTSD), although community participation shows no significant associationwith PTSD. In conclusion, support from family and neighbors plays a vital role in enhancing elderly well-being postdisaster.Policymakers should prioritize strengthening informal support systems to improve the quality of life among the elderly.